2017
DOI: 10.1111/epi.13749
|View full text |Cite
|
Sign up to set email alerts
|

Source localization of ictal epileptic activity based on high‐density scalp EEG data

Abstract: Ictal ESI is a promising localization technique in focal epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 40 publications
(91 reference statements)
4
48
0
1
Order By: Relevance
“…Unfortunately, these gross attempts at classification are far too broad to accurately localize ictal activity for each individual patient. In an attempt to add nuance to their estimates, some studies have further attempted to localize the dominant seizure frequency of the ictal signal at and around the seizure onset [46][47][48][49] . The main shortcoming of these methods is that in order to remove noisy artifacts and improve the SNR, the signal becomes much too smooth (by averaging for instance).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, these gross attempts at classification are far too broad to accurately localize ictal activity for each individual patient. In an attempt to add nuance to their estimates, some studies have further attempted to localize the dominant seizure frequency of the ictal signal at and around the seizure onset [46][47][48][49] . The main shortcoming of these methods is that in order to remove noisy artifacts and improve the SNR, the signal becomes much too smooth (by averaging for instance).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, our 25‐electrode setting was sufficient to record localizable seizure onset activity in 84 of 87 patients. In a recently published study, using a high‐density array for LTM, only 14 of 34 (41%) patients had IC activity, in addition to the II discharges . A recent study suggested that combining ESI with functional connectivity analysis increases its accuracy .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical ESI studies based on II scalp data yielded a high degree of accuracy [6][7][8][10][11][12][13][14][15]. However, only a few studies have addressed IC-EEG signals [9,[16][17][18][19]. IC-ESI faces additional difficulties, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Neue Systeme, die Video-EEG-Aufnahmen mit bis zu 256 Skalpelektroden über 24 h und mehr erlauben, erhöhen die Wahrscheinlichkeit, Anfälle aufzunehmen. Iktale Quellenlokalisation scheint eine gute Lokalisationspräzision sowohl bei extratemporalen als auch temporalen Epilepsien zu haben [17]. Eine klare Diskordanz zu der interiktalen Lokalisation ergab sich nur für 1/14 Patienten.…”
Section: Iktale Quellenanalyseunclassified